2015
DOI: 10.1103/physrevb.92.165408
|View full text |Cite
|
Sign up to set email alerts
|

Layer- and strain-dependent optoelectronic properties of hexagonal AlN

Abstract: Motivated by the recent synthesis of layered hexagonal aluminum nitride (h-AlN), we investigate its layerand strain-dependent electronic and optical properties by using first-principles methods. Monolayer h-AlN is a wide-gap semiconductor, which makes it interesting especially for usage in optoelectronic applications. The optical spectra of 1-, 2-, 3-, and 4-layered h-AlN indicate that the prominent absorption takes place outside the visible-light regime. Within the ultraviolet range, absorption intensities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 75 publications
1
49
0
Order By: Relevance
“…It can be seen from the Fig.10(a) that onset values (the first step-like increase in the figure) of each curves are compatible with the band gap of the structures in Fig.6. It can be explained by the confinement effect related with bond length shrink or stretching which modifies the electronic structure [54].…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from the Fig.10(a) that onset values (the first step-like increase in the figure) of each curves are compatible with the band gap of the structures in Fig.6. It can be explained by the confinement effect related with bond length shrink or stretching which modifies the electronic structure [54].…”
Section: Resultsmentioning
confidence: 99%
“…(iv) The optical-absorption onset energy when going from 3D to 2D GaN is blueshifted, where absorption for g-GaN kicks off within the visible light region or more toward the uv range, differently from 3D wz-and zb-GaN. (v) The evident lower amplitude of the absorption spectrum of g-GaN compared to wz-GaN and zb-GaN is a well-known pattern [65] due to the weaker linear optical response of a single layer of g-GaN, normal to the incident light. This is contrary to bulk wz(zb)-GaN crystals, with periodically repeating multiples of buckled GaN planes along the direction of the lattice constant c. Hence, the optical spectra of monolayer and bulk GaN show significant differences, implying that they could be used for different optoelectronic applications.…”
Section: -7mentioning
confidence: 97%
“…Furthermore, Bacaksiz et al 21 reported that the electronic band structure changes significantly when the number of layer increases and the structure having 10 or more layers exhibits direct bandgap as bulk form. More recently, Kecik et al 33 investigated the optical properties of mono-and few-layer h-AlN under strain. They reported that the absorption peaks stand outside the visible-light regime, on the other hand, the applied tensile strain gradually redshifts the optical spectra.…”
Section: -29mentioning
confidence: 99%